Analisis Pengaruh Partisipasi Penyusunan Anggaran, Kejelasan Anggaran dan Umpan Balik terhadap Peningkatan Kinerja Manajerial melalui Kepuasan kerja dan Ketidakpastian Lingkungan sebagai Variabel Moderating - Noor Azis (Universitas Muria Kudus, 2011)
Target of this research is to analyzed participation in compilation of budget, clarity of feedback and target pass variable satisfaction of job and uncertainty of environment have an effect on directly or indirectly to performance of managerial. This research is conducted by taking sample counted 225 manager or superintendent of distributed manager storey; level counted 800 manager with response rate 38,13% Its enumeration by using SEM Analyzed with processing of AMOS version 5.0 and SPSS version 17. Result of research indicate that participation compilation of budget can be proved by signifikan have positive influence to performance of manajerial through positive impact and signifikan of satisfaction and uncertainty of environment, and so do for the feedback of budget can be proved by signifikan have positive influence to performance of manajerial through positive impact and signifikan of uncertainty of environment, indirect influence other budgeting system characteristic variable, that is participation compilation of budget, clarity of budget target and budget feedback from third itshis only participation variable compilation of shown success budget by signifikan its influence to the increasing of performance of manajerial. While clarity of unprovable target by signifikan have influence to performance of manajerial through positive impact and signifikan of satisfaction and uncertainty of environment, and so do for the feed back of budget nor can be proved by signifikan its influence to performance of manajerial through positive impact and signifikan of satisfaction.